An intelligent postoperative chronic pain prediction system (I-pocpp) - EMRE, İLKİM ECEM (My University, 2022)
Objective: Postoperative Chronic Pain (POCP) affects the quality of patients\" lives. Machine learning and its applications provide significant contributions to pain research. The aim of this study is to predict the POCP status of patients based on perioperative data by developing an \"Intelligent POCP Prediction System (I-POCPP)\" using the best performing machine learning algorithm.
Keywords: TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Postoperative Chronic Pain; Machine Learning; Classification; Decision Support System; MACHINE